Pendampingan Pembelajaran di Madrasah Ibtida’iyah (MI) Tarbiyatul Athfal dengan Tema Model Pembelajaran Al Qur’an dengan Metode Ummi - Khoirul Budi Utomo (Sekolah Tinggi Agama Islam Taruna Surabaya, 2021)
In the learning process, it is an activity that involves the teaching and learning process, especially learning the knowledge of the Koran so that it can realize the capacity to deepen religious knowledge to realize a meaningful, peaceful and dignified life, realizing the importance of the role of Qur'anic knowledge for Muslims. then the values ​​of the knowledge of the Qur'an can be applied in life for every Muslim to become a necessity that must be pursued through education, be it family education, schools, madrasas, al-Qur'an education parks, Islamic boarding schools and so on. Islamic religious education through learning the Qur'an has a very important role in the life of mankind. Religion is a guide in the effort to create a life that is meaningful, peaceful and dignified. Al-Qur'an education is intended to shape students into human beings who believe and devote themselves to God Almighty and have noble morals through the Qur'an. This noble character includes moral ethics as a form of religious education. Increasing spiritual potential includes the introduction, understanding and inculcation of the values ​​of the Koran in individual families or in society. Increasing spiritual potential in deepening the knowledge of al-Qur'an ultimately aims so that humans have dignity as God's creatures. The values ​​in the Qur'an must be instilled in children from an early age as possible as the basis and foundation in carrying out the teachings of Islam. Therefore the objectives of this journal are 1. To describe the strategy or systematics of learning the Ummi method 2. To describe the application of the Ummi method to students at MI Tarbiyatul Athfal 3. To prove the effect of the application of the Ummi method on the ability to read the Koran in students in Tarbiyatul Athfal Madrasah Ibtida'iyah (MI).